All-solid-state thin film battery and preparation method thereof
By adopting all-solid-state thin-film battery structure and simplified preparation process, using raw materials containing S and Na elements, the problems of high cost and low capacity of thin-film battery materials are solved, and high energy density, long life and low cost battery preparation is achieved. .
Patent Information
- Application Number
- CN202411610763.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
Existing thin film batteries have problems such as high material cost, low capacitance, complex manufacturing processes, and difficulty in large areas and mass production.
The all-solid film battery structure is adopted, including the positive electrode current collector layer, the positive electrode layer, the solid electrolyte layer, the negative electrode layer and the negative electrode current collector layer. The coating is carried out by vacuum coating or magnetron sputtering, and raw materials containing S and Na elements are selected. Simplify the preparation process.
It has achieved battery energy density above 500Wh/kg, high rate performance, long life, low material cost, high safety, simple manufacturing process, and large-area and mass production.
Smart Images

Figure CN119481230A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of batteries, and more specifically, to an all-solid-state thin-film battery and a method for preparing the same. Background Art
[0002] The following are the commonly used batteries on the market: 1. Liquid batteries, mainly liquid lithium batteries, use liquid electrolytes and have the advantages of high energy density and long life, but their safety performance is poor and they are prone to fire and cause accidents.
[0003] 2. All-solid-state battery, a battery that uses all-solid-state electrolyte and does not contain liquid components, has the advantages of being non-flammable and non-explosive and having high energy density. However, the grain boundary impedance between the particles in the structure is large and the electron mobility is poor, resulting in poor charging and discharging performance and poor rate performance.
[0004] 3. Thin-film batteries, whose positive and negative electrode materials are the same as those of liquid batteries and all-solid-state batteries, are usually at the micron or nanometer level, and have the advantages of light weight, high energy density, and good safety performance. However, due to their complex manufacturing process and the need for multiple annealing, they are difficult to apply on a large scale, difficult to mass produce, and have small capacity.
[0005] 4. Na-S batteries use sulfur, sodium, etc. as positive and negative electrode materials and have the advantages of low cost, but their operating temperature needs to be controlled at 300-350°C. They are not suitable for rapid start of charging and discharging, so they are only suitable for stationary energy storage and are prone to problems such as thermal runaway.
[0006] Currently, the battery closest to the present invention is a thin film battery. The main defects of existing thin film batteries are: (1) The main materials are lithium or lithium-containing compounds, but lithium resources are limited and the cost is high.
[0007] (2) The capacity is low, mainly due to the limitation of thin film preparation technology. During the preparation process, each coating requires at least one annealing, which usually needs to be performed at a higher temperature, resulting in the inability to prepare batteries on a large scale and in mass production. Most of the batteries produced are the size of a fingernail. Such low capacity limits the application of thin film batteries. Summary of the invention
[0008] In order to reduce the cost of batteries and increase the capacity of batteries so that they can be mass-produced over a large area, the present application provides an all-solid-state thin-film battery and a method for preparing the same.
[0009] In a first aspect, the present application provides an all-solid-state thin-film battery, which adopts the following technical solution: An all-solid-state thin-film battery, comprising a positive electrode current collector layer, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector layer; The positive electrode layer, the solid electrolyte layer, and the negative electrode current collector layer are connected in sequence; The positive electrode current collector layer is arranged on the side of the positive electrode layer away from the solid electrolyte layer, and the negative electrode current collector layer is arranged on the side of the negative electrode layer away from the solid electrolyte layer. Or, the positive electrode current collector layer is arranged on one side of the positive electrode layer, the solid electrolyte layer, and the negative electrode current collector layer, and the negative electrode current collector layer is arranged on the other side of the positive electrode layer, the solid electrolyte layer, and the negative electrode current collector layer; The thickness of the positive electrode layer is 10nm-50μm, and the positive electrode layer is composed of a material containing sulfur and having storage and discharge capabilities; The thickness of the solid electrolyte layer is 10nm-50μm; When the positive electrode layer is composed of a material having storage and discharge capabilities and containing sulfur and metal elements, the thickness of the negative electrode layer is 0nm-50μm; when the positive electrode layer is composed of a material having storage and discharge capabilities and containing sulfur, the thickness of the negative electrode layer is 10nm-50μm; The thickness of the positive electrode current collector layer is 10nm-100μm; When the negative electrode layer is made of a material that is not conductive, the thickness of the negative electrode current collector layer is 10 nm-100 μm; when the negative electrode layer is made of a material that is conductive, the thickness of the negative electrode current collector layer is 0 nm-100 μm.
[0010] Preferably, the weight content of the material having storage and discharge capabilities in the positive electrode layer is 20%-100%, preferably 50%-98%, and more preferably 70%-97%.
[0011] Preferably, the material of the positive electrode layer is one of sodium sulfide, sulfur, a material containing a conductive agent integrated with the aforementioned sodium sulfide or sulfur, a composite compound containing the aforementioned elements, and a sodium battery positive electrode material containing sodium element.
[0012] Preferably, the weight content of the material having storage and discharge capabilities in the negative electrode layer is 50%-100%, preferably 80%-98%, and more preferably 90%-97%.
[0013] Preferably, the material of the negative electrode layer is one of tin, sodium-tin alloys, carbon-based sodium storage materials, composite materials containing sodium storage functional materials, and structures or materials with sodium storage functions integrated with the negative electrode current collector.
[0014] Preferably, the thickness of the positive electrode layer is 40nm-2000nm.
[0015] Preferably, the positive electrode layer is a dense film.
[0016] Preferably, the thickness of the negative electrode layer is 40nm-200nm.
[0017] The core raw materials of this application are raw materials containing S and Na elements. These raw materials are widely available and low in cost, and can effectively reduce battery costs.
[0018] In a second aspect, the present application provides a method for preparing an all-solid-state thin-film battery, using the following technical solution: A method for preparing an all-solid-state thin-film battery, wherein a positive electrode layer, a solid electrolyte layer, and a negative electrode layer are coated by vacuum coating or magnetron sputtering.
[0019] Preferably, any one or more of the positive electrode layer, the solid electrolyte layer and the negative electrode layer of the all-solid-state thin-film battery may be coated by vacuum coating, and the remaining layers may be coated by magnetron sputtering.
[0020] Preferably, when the all-solid-state thin film battery is coated by vacuum evaporation, the preparation method comprises the following steps: Step 1: Set the positive electrode current collector layer as the thin film deposition substrate and evacuate to 1.0×10 -3 Below Pa; Step 2: Adjust the evaporation current, and when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated positive electrode layer material is deposited on the thin film deposition substrate until the cumulative deposition thickness reaches the target thickness, thereby forming a positive electrode layer; Step 3: Adjust the evaporation current, and when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated solid electrolyte layer is deposited on the positive electrode layer until the accumulated deposition thickness reaches the target thickness, thereby forming a solid electrolyte layer; Step 4: adjusting the evaporation current, when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated negative electrode layer is deposited on the solid electrolyte layer material until the cumulative deposition thickness reaches the target thickness, forming a single layer of the negative electrode layer; Step 5: adjusting the evaporation current, when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated negative electrode current collector material is deposited on the negative electrode layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a negative electrode current collector layer; An all-solid-state thin-film battery is obtained.
[0021] Preferably, when the all-solid-state thin film battery is coated by magnetron sputtering, the preparation method comprises the following steps: Step 1: Set the positive electrode current collector layer as the thin film deposition substrate and evacuate to 1.0×10 -3 Pa, and then introduce inert gas; Step 2: Adjust the current power, and when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered positive electrode layer material is deposited on the thin film deposition substrate until the cumulative deposition thickness reaches the target thickness, thereby forming a positive electrode layer; Step 3: Adjust the current power, and when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered solid electrolyte layer is deposited on the positive electrode layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a solid electrolyte layer; Step 4: Adjust the current power, and when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered negative electrode layer is deposited on the solid electrolyte layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a negative electrode layer; Step 5: adjusting the current power, when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered negative electrode current collector material is deposited on the negative electrode layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a negative electrode current collector layer; An all-solid-state thin-film battery is obtained.
[0022] Preferably, when the positive electrode layer and the negative electrode layer of the all-solid-state thin-film battery are coated by vacuum coating, and the solid electrolyte layer is coated by magnetron sputtering, the following steps are included: Step 1: Set the positive electrode current collector layer as the thin film deposition substrate and evacuate to 1.0×10 -3 Below Pa; Step 2: Adjust the evaporation current, and when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated positive electrode layer material is deposited on the thin film deposition substrate until the cumulative deposition thickness reaches the target thickness, thereby forming a positive electrode layer; Step 3: introducing inert gas and adjusting the spray power, when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered solid electrolyte layer is deposited on the positive electrode layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a solid electrolyte layer; Step 4: Stop the inert gas and adjust the evaporation current. When the film thickness change rate reaches 0.1-0.5nm / s, the evaporated negative electrode layer is deposited on the solid electrolyte layer material until the cumulative deposition thickness reaches the target thickness to form a negative electrode layer. The whole is an all-solid-state thin-film battery.
[0023] Room temperature liquid sodium-sulfur (RT Na-S) batteries have been studied as promising energy storage systems due to their high theoretical energy density, low cost, and abundance of sodium and sulfur. However, the inherent electronic insulation of S, the dissolution and shuttling of intermediate sodium polysulfides, and especially the slow conversion kinetics, limit the commercial application of liquid RT Na-S batteries. The volatility of raw materials containing S elements in high vacuum and the inherent slow kinetics have prevented researchers from empirically integrating them into all-solid-state thin-film batteries.
[0024] The present application overcomes the above-mentioned problems by selecting specific raw materials and combining a special preparation method, and can complete the preparation without multiple annealing and without having to operate at a high temperature, thereby enabling the battery to be mass-produced over a large area, giving the thin-film battery a higher capacity.
[0025] In summary, this application has the following beneficial effects: 1. The battery provided in this application has a high energy density, which can exceed 500Wh / kg.
[0026] 2. The battery provided in this application has high rate performance, which can exceed 10C.
[0027] 3. The battery provided in this application has a long life of more than 10,000 cycles.
[0028] 4. The battery materials provided in this application are cheap and low in cost, as low as 0.2 yuan / Wh.
[0029] 5. The batteries provided in this application are safe and completely non-flammable.
[0030] 6. The battery provided in this application has excellent high and low temperature resistance and can be used under conditions of -40℃~80℃.
[0031] 7. The battery manufacturing process provided in this application is simple and can be completed within 2 days.
[0032] 8. The battery provided in this application can be internally connected in series and parallel, can withstand large current and high voltage, and directly form a pack across the module without the need for cumbersome components such as condensation water explosion-proof system. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the structure of the all-solid-state thin-film battery of Example 1.
[0034] Figure 2 The sample after vacuum coating of Example 1 (including 4 Figure 1 All-solid-state thin-film battery with structure).
[0035] Figure 3 This is a charge and discharge curve diagram of the first cycle of the charge and discharge test of the all-solid-state thin-film battery of Example 1. DETAILED DESCRIPTION
[0036] The present application is further described in detail below with reference to the accompanying drawings and embodiments.
[0037] The raw materials used in the following examples and comparative examples are all commercially available products. Example
[0038] An all-solid-state thin-film battery comprises a single layer or multiple layers: a positive electrode current collector layer, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector layer.
[0039] 1. Positive electrode current collector layer: The positive electrode current collector layer can be made of any one of copper foil, aluminum foil, stainless steel foil, composite copper foil, composite aluminum foil, a metal film formed by plating, a composite conductive film, etc., or a mixed combination.
[0040] The thickness thereof may be any one of 10 nm, 100 nm, 1 μm, 5 μm, 10 μm, 50 μm, 100 μm, and the like.
[0041] 2. Positive electrode layer: The positive electrode layer can be made of any one of sodium sulfide, sulfur, lithium sulfide, iron sulfide, zinc sulfide, copper sulfide, polymeric sulfur-containing compounds, etc., or a mixed combination thereof.
[0042] When it is sodium sulfide, it may be sodium sulfide, sodium tetrasulfide, or sodium polysulfide.
[0043] The thickness thereof may be any one of 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 5 μm, 10 μm, 50 μm, etc.
[0044] 3. Solid electrolyte layer: The solid electrolyte layer can be made of sodium phosphate, Na3La(PO4)2, Na-β-Al2O3, Na 1+x Zr2Si x P 3-x O 12 Any one or a mixed combination of the sodium superion conductor (NASICON) type, etc.
[0045] The thickness thereof may be any one of 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 5 μm, 10 μm, 50 μm, etc.
[0046] 4. Negative electrode layer: (1) When the positive electrode layer is composed of a material having storage and discharge capabilities containing sulfur and metal elements, the thickness of the negative electrode layer can be any thickness of 0 nm, 1 nm, 5 nm, 10 nm, 100 nm, 200 nm, 300 nm, 400 nm, 500 nm, 600 nm, 700 nm, 800 nm, 900 nm, 1 μm, 5 μm, 10 μm, 50 μm, etc.
[0047] The material containing sulfur and metal elements and having storage and discharge capabilities may be sodium sulfide, lithium sulfide, potassium sulfide, or sodium polysulfide.
[0048] (2) When the positive electrode layer is composed of a material containing sulfur and having storage and discharge capabilities, the thickness of the negative electrode layer can be any thickness of 10nm, 100nm, 200nm, 300nm, 400nm, 500nm, 600nm, 700nm, 800nm, 900nm, 1μm, 5μm, 10μm, 50μm, etc.
[0049] The material containing sulfur element and having storage and discharge capabilities may be sulfur, polysulfur organic compounds, sodium sulfide, lithium sulfide, potassium sulfide, and sodium polysulfide.
[0050] 5. Negative electrode current collector layer: The negative electrode current collector layer can be made of any one of sodium, tin, sodium-tin alloy, copper, aluminum, etc., or a mixed combination thereof.
[0051] The thickness thereof may be any one of 10 nm, 100 nm, 1 μm, 5 μm, 10 μm, 50 μm, 100 μm, and the like.
[0052] Example 1 Reference Figure 1 , an all-solid-state thin film battery, the thickness of the positive electrode layer Na2S is 500nm, the thickness of the solid electrolyte layer Na3PO4 is 300nm, and the thickness of the negative electrode layer Sn is 100nm. The coating process of the Na2S thin film layer, the Na3PO4 thin film layer, and the Sn thin film layer adopts a magnetron sputtering method.
[0053] The specific steps include: Step 1: Use a three-target magnetron sputtering coating device (model VTC-600-3HD) produced by Shenyang Kejing Automation Equipment Co., Ltd. Install Na2S target sheets (diameter 50mm, thickness 3mm), Na3PO4 target sheets (diameter 50mm, thickness 3mm), and Sn target sheets (diameter 50mm, thickness 3mm) on the three target heads respectively, set copper foil (diameter 100mm, thickness 20μm) on the sample stage as the thin film deposition substrate, and set the mask mold to prepare a sandwich structure with no short circuit in the positive electrode layer / solid electrolyte layer / negative electrode layer. The sample stage is set to rotate at 10 rpm and evacuated to 1.0×10 -3 After the pressure drops below 4 Pa, adjust the device, introduce argon gas at a flow rate of 15 ml / min, and control the vacuum value at about 4 Pa.
[0054] Step 2: Slowly adjust the RF power of the sodium sulfide target to 100W. When the film thickness change rate displayed by the film thickness meter reaches 0.1nm / s, open the sample stage baffle to allow the sputtered sodium sulfide to deposit on the copper foil of the sample stage. When the cumulative deposition thickness reaches 500nm, close the sample stage baffle to reduce the RF power of the sodium sulfide target to zero. At this time, the positive electrode layer is formed.
[0055] Step 3: While controlling the vacuum value at about 4.0Pa, introduce nitrogen gas at a flow rate of 15 ml / min, slowly adjust the RF power of the sodium phosphate target to 100W, and when the film thickness change rate displayed by the film thickness meter reaches 0.1nm / second, open the sample stage baffle to allow the sputtered sodium phosphate to continue to deposit on the copper foil of the sample stage. When the cumulative deposition thickness reaches 300nm, close the sample stage baffle and reduce the RF power of the sodium phosphate target to zero. At this time, a solid electrolyte layer covering the positive electrode layer is formed.
[0056] Step 4: Turn off the nitrogen. Slowly adjust the RF power of the tin target to 50W. When the film thickness change rate displayed by the film thickness meter reaches 0.1nm / second, open the sample stage baffle to allow the sputtered tin to continue to deposit on the copper foil of the sample stage. When the cumulative deposition thickness reaches 100nm, close the sample stage baffle and reduce the RF power of the tin target to zero. At this time, a negative electrode layer is formed on the solid electrolyte layer.
[0057] Step 5: Place the vacuum coated copper foil ( Figure 2 , including 4 Figure 1 The structure of the sample obtained after cutting is shown in the figure below. Figure 1 (The plane area of the positive electrode film layer and the negative electrode film layer is 1cm 2 ).
[0058] The copper foil is used as the positive electrode collector layer to lead out the positive electrode tab, and the tin layer is used as the negative electrode collector layer to lead out the negative electrode tab, and an aluminum-plastic film small soft-pack battery, i.e., an all-solid-state thin-film battery, is manufactured in a glove box with an argon atmosphere (water content less than 0.1ppm, oxygen content less than 0.1ppm).
[0059] Performance testing: The thickness of each deposited material was obtained by a film thickness meter, and theoretical calculations showed that the weight of sodium sulfide in the battery was 9.3ug, the weight of sodium phosphate was 48.6ug, and the weight of tin was 72.8ug.
[0060] Use the battery charge and discharge system (SLAN-CT2001A battery tester) to perform charge and discharge tests on small soft-pack batteries.
[0061] The first cycle charging current is 0.5uA, and the discharge current is 0.5uA. The test results show that the charging capacity of the positive electrode material of the first cycle of this battery is 460mAh / g, the discharge capacity is 391mAh / g, and the coulomb efficiency is 85%. The charge and discharge curve is as follows Figure 3 shown.
[0062] The second cycle charging current is 1uA, and the discharge current is 1uA. The second cycle discharge capacity is 421mAh / g, and the coulomb efficiency is 96%. The third cycle has a charging current of 1uA and a discharging current of 2.5uA. The third cycle has a discharging capacity of 378mAh / g and a coulombic efficiency of 95%.
[0063] The fourth cycle has a charging current of 1uA and a discharging current of 1uA. After 100 times of repeated discharge under the same charging and discharging conditions, the 103rd cycle has a charging capacity of 398mAh / g, a discharging capacity of 390mAh / g, and a coulombic efficiency of 98%.
[0064] Compared with the discharge capacity of the second cycle, the discharge capacity maintenance rate of the third cycle is 90%, indicating that the discharge rate performance is good after the discharge current is increased by 2.5 times.
[0065] The discharge capacity at the 103rd cycle was maintained at 92% compared with the discharge capacity at the 4th cycle, indicating that the cycle performance was good after 100 cycles of charge and discharge.
[0066] Using the total weight of the deposited material in the battery as well as the discharge capacity and average discharge voltage of the second cycle, the energy density of the battery was calculated to be 491Wh / kg.
[0067] Example 2 An all-solid-state thin-film battery comprises a positive electrode current collector, a positive electrode layer, a solid electrolyte layer and a negative electrode layer.
[0068] The material of the positive electrode layer is Na2S, with a thickness of 1000nm, which is a dense film; the material of the solid electrolyte layer is Na3PO4, with a thickness of 300nm; the material of the negative electrode layer is Sn, with a thickness of 300nm. The coating process of the Na2S thin film layer, the Na3PO4 thin film layer, and the Sn thin film layer adopts the evaporation coating method.
[0069] The following steps are involved: Step 1: Use the evaporation vacuum coating machine (model GSL-1800X-ZF4) produced by Shenyang Kejing Automation Equipment Co., Ltd., place sodium sulfide powder, sodium phosphate powder, and tin powder on three tungsten boats as evaporation source targets, set copper foil (diameter 100mm, thickness 20μm) on the sample stage as the thin film deposition substrate, and set the mask mold to prepare a sandwich structure with a positive electrode layer / solid electrolyte layer / negative electrode layer without short circuit. The sample stage is set to rotate at 10 rpm and evacuate to 1.0×10 -3 Below Pa.
[0070] Step 2: Slowly adjust the evaporation current of the sodium sulfide evaporation target to 50A. When the film thickness change rate displayed by the film thickness meter reaches 0.2nm / second, open the sample stage baffle to allow the evaporated sodium sulfide to be deposited on the copper foil of the sample stage. When the cumulative deposition thickness reaches 500nm, close the sample stage baffle to reduce the evaporation current of the sodium sulfide target to zero. At this time, the positive electrode layer is formed.
[0071] Step 3: Slowly adjust the evaporation current of the sodium phosphate evaporation target to 20A. When the film thickness change rate displayed by the film thickness meter reaches 0.2nm / second, open the sample stage baffle to allow the evaporated sodium phosphate to continue to deposit on the copper foil of the sample stage. When the cumulative deposition thickness reaches 300nm, close the sample stage baffle to reduce the evaporation current of the sodium phosphate target to zero. At this time, a solid electrolyte layer covering the positive electrode layer is formed.
[0072] Step 4: Slowly adjust the evaporation current of the tin evaporation target to 80A. When the film thickness change rate displayed by the film thickness meter reaches 0.2nm / second, open the sample stage baffle to allow the evaporated tin to continue to deposit on the copper foil of the sample stage. When the cumulative deposition thickness reaches 100nm, close the sample stage baffle to reduce the evaporation current of the tin target to zero. At this time, a negative electrode layer located on the solid electrolyte layer is formed.
[0073] Step 5: Cut the copper foil vacuum-coated in step 4.
[0074] The copper foil is used as the positive electrode collector layer to lead out the positive electrode tab, and the tin layer is used as the negative electrode collector layer to lead out the negative electrode tab, and an aluminum-plastic film small soft-pack battery, i.e., an all-solid-state thin-film battery, is manufactured in a glove box with an argon atmosphere (water content less than 0.1ppm, oxygen content less than 0.1ppm).
[0075] Performance testing: The thickness of the film layer was obtained by a film thickness meter, and theoretical calculations showed that the weight of sodium sulfide in the battery was 18.6 ug, the weight of sodium phosphate was 48.6 ug, and the weight of tin was 218 ug.
[0076] Use the battery charge and discharge system (SLAN-CT2001A battery tester) to perform charge and discharge tests on small soft-pack batteries.
[0077] The first cycle charging current is 0.5uA, and the discharge current is 0.5uA. The test results show that the first cycle charging capacity of this battery is 345mAh / g, the discharge capacity is 283mAh / g, and the coulombic efficiency is 82%.
[0078] The second cycle charging current is 1uA, and the discharge current is 1uA. The second cycle discharge capacity is 313mAh / g, and the coulomb efficiency is 95%.
[0079] The third cycle has a charging current of 1uA and a discharging current of 2.5uA. The third cycle has a charging capacity of 466mAh / g, a discharging capacity of 278mAh / g, and a coulombic efficiency of 93%.
[0080] The fourth cycle has a charging current of 1uA and a discharging current of 1uA. After 100 times of repeated discharge under the same charging and discharging conditions, the 103rd cycle has a charging capacity of 295mAh / g, a discharging capacity of 298mAh / g, and a coulombic efficiency of 99%.
[0081] Compared with the discharge capacity of the second cycle, the discharge capacity maintenance rate of the third cycle is 88%, indicating that the discharge rate performance is good after the discharge current is increased by 2.5 times.
[0082] The discharge capacity at the 103rd cycle was maintained at 94% compared with the discharge capacity at the 4th cycle, indicating that the cycle performance was good after 100 cycles of charge and discharge.
[0083] Using the weight of the deposited material in the battery as well as the discharge capacity and average discharge voltage of the second cycle, the energy density of the battery was calculated to be 348Wh / kg.
[0084] Example 3 An all-solid-state thin film battery, wherein the Na2S layer has a thickness of 1500nm, the Na3PO4 layer has a thickness of 500nm, and the Sn layer has a thickness of 300nm. The Na3PO4 layer is prepared by the magnetron sputtering coating method of Example 1, and the Na2S layer and the Sn layer are prepared by the evaporation coating method of Example 2. Other operating methods are the same as those of Example 1 and are not described herein.
[0085] Performance testing: The thickness of the film layer was obtained by a film thickness meter, and theoretical calculations showed that the weight of sodium sulfide in the battery was 27.9 ug, the weight of sodium phosphate was 8.1 ug, and the weight of tin was 218 ug.
[0086] Use the battery charge and discharge system (SLAN-CT2001A battery tester) to perform charge and discharge tests on small soft-pack batteries.
[0087] The first cycle charging current is 0.5uA, and the discharge current is 0.5uA. The test results show that the first cycle charging capacity of this battery is 414mAh / g, the discharge capacity is 352mAh / g, and the coulombic efficiency is 85%.
[0088] The second cycle has a charge current of 1uA and a discharge current of 1uA. The second cycle has a charge capacity of 395mAh / g, a discharge capacity of 379mAh / g, and a coulombic efficiency of 96%.
[0089] The third cycle has a charging current of 1uA and a discharging current of 2.5uA. The third cycle has a discharging capacity of 340mAh / g and a coulombic efficiency of 95%.
[0090] The fourth cycle has a charging current of 1uA and a discharging current of 1uA. After 100 times of repeated discharge under the same charging and discharging conditions, the 103rd cycle has a capacity of 358mAh / g, a discharge capacity of 351mAh / g, and a coulombic efficiency of 98%.
[0091] Compared with the discharge capacity of the second cycle, the discharge capacity maintenance rate of the third cycle is 89%, indicating that the discharge rate performance is good after the discharge current is increased by 2.5 times.
[0092] The discharge capacity at the 103rd cycle was maintained at 92% compared with the discharge capacity at the 4th cycle, indicating that the cycle performance was good after 100 cycles of charge and discharge.
[0093] Using the weight of the deposited material in the battery as well as the discharge capacity and average discharge voltage of the second cycle, the energy density of the battery was calculated to be 491Wh / kg.
[0094] Example 4 An all-solid-state thin film battery, which is different from Example 1 in that the thickness of the S layer is 300nm, the thickness of the Na3PO4 layer is 500nm, and the thickness of the NaSn alloy layer is 1000nm. The preparation method of the all-solid-state thin film battery is the same as that of Example 1, except that the S target is used instead of the Na2S target and the NaSn alloy target is used instead of the Sn target, and is not described here.
[0095] Performance testing: The thickness of the film layer was obtained by a film thickness meter, and theoretical calculations showed that the weight of sulfur in the battery was 70.8 ug, the weight of sodium phosphate was 8.1 ug, and the weight of sodium-tin alloy was 96.8 ug.
[0096] Use the battery charge and discharge system (SLAN-CT2001A battery tester) to perform charge and discharge tests on small soft-pack batteries.
[0097] The first cycle charging current is 0.5uA, and the discharge current is 0.5uA. The test results show that the first cycle charging capacity of this battery is 1065mAh / g, the discharge capacity is 905mAh / g, and the coulombic efficiency is 85%.
[0098] The second cycle has a charging current of 1uA and a discharging current of 1uA. The second cycle has a charging capacity of 1017mAh / g, a discharging capacity of 976mAh / g, and a coulombic efficiency of 96%.
[0099] The third cycle has a charging current of 1uA and a discharging current of 2.5uA. The third cycle has a charging capacity of mAh / g, a discharging capacity of 876mAh / g, and a coulombic efficiency of 95%.
[0100] The fifth cycle has a charging current of 1uA and a discharging current of 1uA. After 100 times of repeated discharge under the same charging and discharging conditions, the 103rd cycle has a capacity of 922mAh / g, a discharge capacity of 903mAh / g, and a coulombic efficiency of 98%.
[0101] Compared with the discharge capacity of the second cycle, the discharge capacity maintenance rate of the third cycle is %, indicating that the discharge rate performance is good after the discharge current is increased by 5 times.
[0102] Compared with the discharge capacity of the second cycle, the discharge capacity maintenance rate of the fourth cycle is 90%, indicating that the discharge rate performance is good after the discharge current is increased by 2.5 times.
[0103] The discharge capacity at the 103rd cycle was maintained at 92% compared with the discharge capacity at the 4th cycle, indicating that the cycle performance was good after 100 cycles of charge and discharge.
[0104] Using the weight of the deposited material in the battery, the discharge capacity of the second cycle, and the average discharge voltage, the energy density of the battery was calculated to be 747 Wh / kg.
[0105] Comparative Example 1 An all-solid-state thin-film battery, which is different from Example 1 in that the coating time of the positive electrode layer is prolonged and the thickness of the obtained positive electrode layer is 75 μm. The rest is the same as Example 1 and will not be described here.
[0106] The battery performance test was carried out using the same battery test method as in Example 1. The first cycle charge capacity of the battery was 69 mAh / g, the discharge capacity was 44 mAh / g, and the coulombic efficiency was 64%.
[0107] Comparative test results show that increasing the thickness of the positive electrode thin film layer to 75μm significantly reduces the battery performance of the thin film battery.
[0108] Comparative Example 2 An all-solid-state thin-film battery, which is different from Example 1 in that the coating time of the solid electrolyte layer is prolonged during the coating stage, and the thickness of the solid electrolyte layer is 75 μm. Others are the same as Example 1, which will not be described here.
[0109] The battery performance test was carried out using the same battery test method as in Example 1. The first cycle charge capacity of the battery was 23 mAh / g, the discharge capacity was 7 mAh / g, and the coulombic efficiency was 30%.
[0110] Comparative test results show that increasing the thickness of the solid electrolyte layer to 75μm significantly reduces the battery performance of the resulting thin-film battery.
[0111] Comparative Example 3 An all-solid-state thin-film battery, which is different from Example 1 in that the coating time of the negative electrode layer is prolonged and the thickness of the negative electrode layer is 75 μm. Others are the same as Example 1 and will not be described here.
[0112] The battery performance test was carried out using the same battery test method as in Example 1. The first cycle charge capacity of the battery was 115 mAh / g, the discharge capacity was 3 mAh / g, and the coulombic efficiency was 3%.
[0113] Comparative test results show that increasing the thickness of the negative electrode film layer to 75μm significantly reduces the battery performance of the thin film battery.
[0114] The commonly used wet coating method and related process equipment on the market can only produce a film layer with a thickness of about 10μm or more, and cannot produce a thinner film of the content of the present application. The all-solid-state battery with a thickness of 100μm was prepared using the wet coating method and related process equipment and Na2S as the positive electrode active material, but the charging and discharging performance effect of the present application could not be obtained, and the all-solid-state thin film battery of the present application could not be obtained.
[0115] In summary, the all-solid-state thin-film battery prepared using the technical solution provided in this application has a very high battery energy density, far exceeding the products on the market. In addition, during repeated charge and discharge, it exhibits excellent discharge rate and cycle properties, effectively improving the battery capacity.
[0116] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An all-solid-state thin-film battery, characterized in that: It comprises a positive electrode current collector layer, a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode current collector layer; The positive electrode layer, the solid electrolyte layer, and the negative electrode current collector layer are connected in sequence; The positive electrode current collector layer is arranged on the side of the positive electrode layer away from the solid electrolyte layer, and the negative electrode current collector layer is arranged on the side of the negative electrode layer away from the solid electrolyte layer. Or, the positive electrode current collector layer is arranged on one side of the positive electrode layer, the solid electrolyte layer, and the negative electrode current collector layer, and the negative electrode current collector layer is arranged on the other side of the positive electrode layer, the solid electrolyte layer, and the negative electrode current collector layer; The thickness of the positive electrode layer is 10nm-50μm, and the positive electrode layer is composed of a material containing sulfur and having storage and discharge capabilities; The thickness of the solid electrolyte layer is 10nm-50μm; When the positive electrode layer is composed of a material having storage and discharge capabilities and containing sulfur and metal elements, the thickness of the negative electrode layer is 0nm-50μm; when the positive electrode layer is composed of a material having storage and discharge capabilities and containing sulfur, the thickness of the negative electrode layer is 10nm-50μm; The thickness of the positive electrode current collector layer is 10nm-100μm; When the negative electrode layer is made of a material that has no conductivity, the thickness of the negative electrode current collector layer is 10 nm-100 μm; when the negative electrode layer is made of a material that has conductivity, the thickness of the negative electrode current collector layer is 0 nm-100 μm.
2. The all-solid-state thin-film battery according to claim 1, characterized in that: The weight content of the material with storage and discharge capabilities in the positive electrode layer is 20%-100%.
3. The all-solid-state thin-film battery according to claim 1, characterized in that: The material of the positive electrode layer is one of sodium sulfide, sulfur, a material containing a conductive agent and integrated with the aforementioned sodium sulfide or sulfur, a composite compound containing the aforementioned elements, and a sodium battery positive electrode material containing sodium element.
4. The all-solid-state thin-film battery according to claim 1, characterized in that: The weight content of the material with storage and discharge capabilities in the negative electrode layer is 50%-100%.
5. The all-solid-state thin-film battery according to claim 1, characterized in that: The material of the negative electrode layer is one of tin, sodium-tin alloy, carbon sodium storage material, composite material containing sodium storage functional material, and structure or material with sodium storage function integrated with the negative electrode current collector.
6. The all-solid-state thin-film battery according to claim 1, characterized in that: The positive electrode layer is a dense film.
7. A method for preparing an all-solid-state thin-film battery according to any one of claims 1 to 6, characterized in that: The positive electrode layer, the solid electrolyte layer and the negative electrode layer are plated by vacuum coating or magnetron sputtering.
8. The all-solid-state thin-film battery according to claim 7, characterized in that: When the all-solid-state thin film battery is coated by vacuum evaporation, the preparation method comprises the following steps: Step 1: Set the positive electrode current collector layer as the thin film deposition substrate and evacuate to 1.0×10 -3 Below Pa; Step 2: Adjust the evaporation current, and when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated positive electrode layer material is deposited on the thin film deposition substrate until the cumulative deposition thickness reaches the target thickness, thereby forming a positive electrode layer; Step 3: Adjust the evaporation current, and when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated solid electrolyte layer is deposited on the positive electrode layer until the accumulated deposition thickness reaches the target thickness, thereby forming a solid electrolyte layer; Step 4: adjusting the evaporation current, when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated negative electrode layer is deposited on the solid electrolyte layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a negative electrode layer; Step 5: adjusting the evaporation current, when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated negative electrode current collector material is deposited on the negative electrode layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a negative electrode current collector layer; An all-solid-state thin-film battery is obtained.
9. The all-solid-state thin-film battery according to claim 7, characterized in that: When the all-solid-state thin-film battery is coated by magnetron sputtering, the preparation method comprises the following steps: Step 1: Set the positive electrode current collector layer as the thin film deposition substrate and evacuate to 1.0×10 -3 Pa, and then introduce inert gas; Step 2: Adjust the current power, and when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered positive electrode layer material is deposited on the thin film deposition substrate until the cumulative deposition thickness reaches the target thickness, thereby forming a positive electrode layer; Step 3: Adjust the current power, and when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered solid electrolyte layer is deposited on the positive electrode layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a solid electrolyte layer; Step 4: adjusting the current power, when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered negative electrode layer is deposited on the solid electrolyte layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a negative electrode layer; Step 5: Adjust the current power. When the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered negative electrode current collector material is deposited on the negative electrode layer material until the cumulative deposition thickness reaches the target thickness to form a negative electrode current collector layer; and obtain an all-solid-state thin film battery.
10. The all-solid-state thin-film battery according to claim 7, characterized in that: When the positive electrode layer and the negative electrode layer of the all-solid-state thin film battery are coated by vacuum coating, and the solid electrolyte layer is coated by magnetron sputtering, the following steps are included: Step 1: Set the positive electrode current collector layer as the thin film deposition substrate and evacuate to 1.0×10 -3 Below Pa; Step 2: Adjust the evaporation current, and when the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated positive electrode layer material is deposited on the thin film deposition substrate until the cumulative deposition thickness reaches the target thickness, thereby forming a positive electrode layer; Step 3: introducing inert gas and adjusting the spray power, when the film thickness change rate reaches 0.1-0.5 nm / s, the sputtered solid electrolyte layer is deposited on the positive electrode layer material until the cumulative deposition thickness reaches the target thickness, thereby forming a solid electrolyte layer; Step 4: Stop the inert gas and adjust the evaporation current. When the film thickness change rate reaches 0.1-0.5 nm / s, the evaporated negative electrode layer is deposited on the solid electrolyte layer material until the cumulative deposition thickness reaches the target thickness to form a negative electrode layer; and an all-solid-state thin film battery is obtained.
Citation Information
Patent Citations
All-solid-state sodium-sulfur battery and preparation method thereof
CN110649314A
Amorphous ferrous sulfide positive electrode thin film material, preparation method thereof and all-solid-state thin film lithium battery
CN115249806A
Protective sacrificial coating to enhance stability of battery materials
US20200395630A1
Cited By
All-solid-state thin film battery and production process thereof
CN120473576A
Thin film all-solid-state battery and preparation method thereof
CN120497470A
Sodium sulfide all-solid-state battery
CN120690947A